Molecular and functional characterization of Accl(2)efl: A biomarker for heavy metal stress in Apis cerana cerana - Yu-Lin Xu; Ling Peng; Jun-Jie Li; Wen-Feng Chen (Ecotoxicology and Environmental Safety)
The expanded lethal (2) essential for life [l(2)efl] gene family is responsive to proteostatic stresses. Their protein products are core components of the stress response mechanism and are emerging as promising biomarkers for cellular stress in Apis mellifera. However, l(2)efl (LOC410857) uniquely remains unresponsive to heat stress within this gene family, and research examining its role in adaptation to other types of stress across diverse bee species is scarce. To address this knowledge gap, we cloned the l(2)efl gene from Apis cerana cerana [Accl(2)efl] and conducted a bioinformatics analysis on the encoded protein, aiming to elucidate the potential functions of Accl(2)efl. Our study encompassed assessing the role of Accl(2)efl in the response of bees to various stressful environments and its involvement in tolerance to heavy metals (Cd and Hg). Furthermore, we employed the RNAi technology to delve into the response mechanisms of Accl(2)efl under Cd and Hg stress. Our findings revealed that Accl(2)efl was activated when exposed to CdCl2 or HgCl2. Following the knockdown of Accl(2)efl, we observed that genes, such as defensins, were upregulated through the activation of the Toll signaling pathway. Conversely, the peroxisome signaling pathway was inhibited, resulting in a notable decrease in antioxidant enzyme activity. This led to a substantial elevation in Cd and Hg concentrations within hemolymph, accompanied by an increased mortality rate among bees re-exposed to CdCl2 or HgCl2. Combined, our data indicated that Accl(2)efl may plays a role in the tolerance of Apis cerana cerana to Cd/Hg stress. These findings provide a scientific basis for the further exploration of the role of Accl(2)efl in the response of bees to Cd/Hg stress and for enhancing the anti-Cd/Hg stress signaling network. They further lay a theoretical foundation for identifying new stress biomarkers for bees as well as indicators for the detection of environmental pollution.